The girl who stopped swimming [compact disc, unabridged] - Jackson, Joshilyn (Hachette Audio, 2008)
Laurel Gray Hawthorne needs to make things pretty but her estranged sister Thalia, an impoverished actress with a capital A, is her polar opposite, priding herself on exposing the lurid truth lurking behind middle class niceties. One night Laurel is visited by the ghost of a her 13-year old neighbor Molly Dufresne. The ghost leads Laurel to the real Molly floating lifelessly in the Hawthorne's backyard pool. She enlists Thalia's help and Laurel sets out on a life-altering journey that triggers startling revelations about her family's guarded past, the true state of her marriage, and the girl who stopped swimming.